EFEKTIVITAS FUNGSI LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN (LPMK) DI KELURAHAN LEMBAH DAMAI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU - Fauza Amelia; Zaili Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study explains about the Effectiveness of Lembaga Pemberdayaan Masyarakat Kelurahan (LPMK) functions at Lembah Damai Village, Rumbai Pesisir District, Pekanbaru. While the background of this study is to see the effectiveness of LPMK Lembah Damai in actuating its function in the society. This study was based on the result of interview and observation as the writer’s initial data which found indications of problems, those are the persistence of the development program that has not been realized, lack of community participations, the thuggery actions, and less activation of LPMK management. The purpose of this study is to analyze the Effectiveness of Lembaga Pemberdayaan Masyarakat Kelurahan (LPMK) Functions at Lembah Damai Village, Rumbai Pesisir District, Pekanbaru.The writer used the theory of Richard M. Steers which consists of, ability to adapt, work productivity, job satisfaction, and resource utilization. Research Methodology of this study is descriptive with the data collection technique through literature review and field study (observation and interview).The conclusion of this study shows that the function of LPMK at Lembah Damai village is not effective yet. In compiling the aspirations of society, LPMK has been able to accommodate, formulate, and convey the aspirations of society in development through Musrenbang. But, the ability of resources of LPMK management is still low and the participation of the society in giving proposal and ideas is still pasive. The suggestion from the writer to LPMK at Lembah Damai village in empowering function is LPMK in Lembah Damai village should first be able to strengthen the position of LPMK as village’s partner organizations and government officials to accommodate and satisfy the aspirations of the people in the field of development.Key words : The Effectiveness, Functions, LMPK.